Penerapan Algoritma C4.5 Untuk Memprediksi Keuntungan Pada PT SMOE Indonesia - Tukino, Tukino (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
In the construction project activities, planning is used as a reference for job implementers and becomes the standard of project implementation, including: documents, technical specifications, schedule and budget. Inappropriate planning, inaccurate project realization investigations, inadequate project management skills and lack of professional service providers, are closely related to the outcome of a construction project process. PT SMOE Indonesia which is a company engaged in construction consulting services. At the present time PT SMOE Indonesia has done many construction planning projects both from government and private, this research will discuss how data mining with algorithm C4.5 process data from budget plan consultant planner cost to predict company profit. Data mining is a technique for extracting new information from piles or data warehouses, as we know information is seen as something that is very important and valuable because by mastering information it is easy to achieve a desired goal, this makes everyone race to while C4.5 algorithm is one of induction algorithm of decision tree that is ID3 (Iterative Dichotomiser 3). ID3 was developed by J. Ross Quinlan. In the ID3 algorithm procedure, the inputs are training samples, training labels and attributes. which will illustrate the profit prediction, the results of this study will result in the rules of profit and loss decisions company.